The lamellar-to-isotropic transition in ternary amphiphilic systems - Schwarz, Ulrich S.; Swamy, K.; Gompper, Gerhard (Arxiv, 1996)
We study the dependence of the phase behavior of ternary amphiphilic systems on composition and temperature. Our analysis is based on a curvature elastic model of the surfactant film with sufficiently large spontaneous curvature and sufficiently negative saddle-splay modulus that the stable phases are the lamellar phase and a droplet microemulsion. In addition to the curvature energy, we consider the contributions to the free energy of the long-ranged van der Waals interaction and of the undulation modes. We find that for bending rigidities of order k_B T, the lamellar phase extends further and further into the water apex of the phase diagram as the phase inversion temperature is approached, in good agreement with experimental results.
Gesehen am 18.12.2017